ANALISIS PENGARUH VARIASI JUMLAH SUDU TERHADAP KINERJA TURBIN CROSSFLOW DI PT XYZ - Farhan Rahmat Putra; Andre Kurniawan; Yolli Fernanda; Randi Purnama Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effect of blade number variation on the performance of a crossflow turbine used in the Micro-Hydro Power Plant (PLTMH) system at PT XYZ. The research was conducted using a numerical simulation approach based on Computational Fluid Dynamics (CFD) with Solidworks 2022 for geometry modeling and ANSYS Fluent 2025 R1 for fluid flow simulation. The variations of blade numbers investigated were 18, 24, 30, and 32 blades, with constant operating parameters including a flow rate of 0.03678 m³/s, a head of 0.3 m, and a rotational speed of 1500 rpm. The simulation results indicate that the number of blades significantly affects the torque, output power, and efficiency of the crossflow turbine. The configuration with 18 blades produced the best performance, achieving a torque of 21.39 Nm, an effective power of 3359.64 W, and an efficiency of 31.09%, while configurations with 24 and 32 blades showed a significant decrease in efficiency to around 6%. The analysis of velocity contours, pressure contours, and streamlines revealed that the 18-blade configuration provides a more stable and focused flow with uniform pressure distribution along the blade’s leading edge, resulting in greater tangential force on the runner shaft. In contrast, increasing the number of blades causes higher turbulence and energy losses. Therefore, it can be concluded that the 18-blade configuration is the most optimal design for achieving efficient crossflow turbine performance under the specified operating conditions.